Large wood potential, piece characteristics, and flood effects in Swiss mountain streams. (2nd November 2018) - Rickli, Christian; Badoux, Alexandre; Rickenmann, Dieter; Steeb, Nicolas; Waldner, Peter
Abstract: We present results of two studies on the (1) potential wood load in steep headwater streams and (2) properties of large wood (LW) transported in mountain rivers during the large August 2005 flood event in Switzerland. Ten headwater reaches of 1000 m length were surveyed in different regions of Switzerland. The potential wood load was estimated for in-channel deadwood, and possible driving factors were explored. Correlations were found with dead wood volume on hillslopes and mean channel width. We established size distributions of LW pieces and identified probable recruitment processes. Four reaches were resurveyed after an exceptionally severe flood in August 2005, showing limited LW transport in channels but considerable wood input by mass wasting processes. In addition, characteristics of deposits of LW along mountain rivers affected by the 2005 flood were investigated. Diameter and length distribution of transported and deposited pieces were comparable to those of LW from steep headwater streams, yet with considerably fewer long pieces in the deposits of mountain rivers. Most LW pieces were fresh wood, indicating that the portion of in-channel deadwood transported during the 2005 flood was limited. Findings of the study contribute to a better understanding of LW dynamics in Alpine mountain streams.